Measurement of Kampung Performance as Basic Strategy Towards a Resilient City: Evidence from CASBEE-UD and LEED-ND`s Results - Roychansyah, Muhammad Sani (RUAS, 2012)
Urban kampung is body and soul of Indonesia urban structure and life. It has vital roles for social, economy, and physical strategies, including a resilient city strategy. That is why kampung oriented development (KOD) would be inevitably an underlying model to bring kampung towards sustainable urban development. As an investigation step, it is important to assess their environmental performance conditions, using popular and leading sustainable building and assessment tools to measure the conditions of existing urban kampungs. (Comprehensive Assessment System for Building Environmental Efficiency for Urban Development)and LEED-ND (Leadership in Energy & Environmental Design for Neighborhood Development) are chosen and applied to critically observe the kampung environment conditions comprehensively. Results showed in average that the urban kampungs in term of environmental performance based on both CASBEE-UD and LEED-ND category are still quite far from the ideal criteria. These results significantly steer a road map of strategies related to kampung oriented development (KOD).Keywords: compactness, kampung oriented development, CASBEE-UD, LEED-ND